2004
DOI: 10.1007/978-3-540-30117-2_90
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Acceleration of Rigid Molecule Interactions

Abstract: Modeling of molecule interactions often uses two or more successive models of increasing complexity. Rigid models based on correlation techniques are common as early screening passes-to detect interactions worth costlier examination-and are often at the heart of later passes as well. Even these rigid models are time-consuming when applied to large models at 10 3 − 10 5 different three-axis rotations. This paper presents an FPGA structure for performing the correlations efficiently by using a systolic array for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…There are recent efforts on applying FPGAs as accelerators for parallel data analytics (Court et al, 2004;Ronan et al, 2006;Woods & Van Court, 2008). Shan et.al present a framework to use FPGAs to accelerate MapReduce processing in (Shan et al, 2010).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There are recent efforts on applying FPGAs as accelerators for parallel data analytics (Court et al, 2004;Ronan et al, 2006;Woods & Van Court, 2008). Shan et.al present a framework to use FPGAs to accelerate MapReduce processing in (Shan et al, 2010).…”
Section: Related Workmentioning
confidence: 99%
“…FPGAs are considered to be powerful computation devices and suited as accelerators for b ig data analytics. It is common for many applications to employ FPGA based devices to accelerate their performance (e.g., (Court, Gu & Herbordt, 2004;Ronan, Éigeartaigh, Murphy, Scott & Kerins, 2006;Woods & VanCourt, 2008)). FPGAs are also deployed in the cloud environment as accelerators for large scale data processing such as MapReduce (Shan, Wang, Yan, Wang, Xu & Yang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Non-intersection Poor fit Figure 2: Shape complementarity, collisions, misses, and poor matches (from [10]). …”
Section: Close Shape Complementarity Collisionmentioning
confidence: 99%
“…The introduction of the FFT to docking [6] reduced the complexity of each 3D correlation to Ç´AE ¿ ÐÓ AEµ for steric (shape only) models; further work expanded the method to electrostatic [3] and solvation contributions [1]. In previous work [10,11] we showed that, for FPGAbased coprocessors, the original direct correlationrather than an FFT-is sometimes the preferred method for computing rigid molecule docking. Two reasons for this are the inherent efficiency with which FPGAs perform convolutions and the modest precision (2-7 bits) of the original voxel data.…”
Section: Close Shape Complementarity Collisionmentioning
confidence: 99%
“…Finally, this work is part of a larger project involving the acceleration of applications in computational biochemistry (e.g. [14]) and will be integrated into that.…”
Section: Optimizations and Extensionsmentioning
confidence: 99%